The Discourse and Value of Being an Independent Publisher - Noorda, Rachel (Mémoires du livre / Studies in Book Culture, 2019)
Publishing did not have independents enter self-discourse until the 1960s when media conglomeration created a need to distinguish other publishers from this network of corporate giants. But rather than decimating the independent publishing landscape, the corporate conglomeration of book publishing has opened a space for independent publishers to thrive (Simon and McCarthy, 2009; Schiffrin, 2001; Hawthorne, 2014, 2016; Kogan 2007, 2010), in part because of the social currency that positioning themselves as independent in discourse affords. In order to analyze the use, purpose, and meaning of independent in publisher discourse, this article conducts a content analysis on mission statements of 39 US-based independent publishers. Through content analysis of mission statements, this article illuminates the way that certain publishers construct a particular social function and marketing appeal by the use of independent in twenty-first century book publishing discourse in the US.